Why do I need a teacher when I've got Google? the essential guide to the big issues for every teacher - Gilbert, Ian 1965- (London Routledge, 2014)
"Why do I need a teacher when I've got Google? is just one of the challenging, controversial and thought-provoking questions Ian Gilbert poses in this urgent and invigorating book. Questioning the unquestionable, this fully updated new edition will make you re-consider everything you thought you knew about teaching and learning, such as: - Are you simply preparing the next generation of unemployed accountants? - What do you do for the 'sweetcorn kids' who come out of the education system in pretty much the same state as when they went in? - What's the real point of school? - Exams - So whose bright idea was that? - Why 'EQ' is fast becoming the new 'IQ'. - What will your school policy be on brain-enhancing technologies? - Which is the odd one out between a hamster and a caravan? With his customary combination of hard-hitting truths, practical classroom ideas and irreverent sense of humour, Ian Gilbert takes the reader on a breathless rollercoaster ride through burning issues of the twenty-first century, considering everything from the threats facing the world and the challenge of the BRIC economies to the link between eugenics and the 11+. As wide-ranging and exhaustively-researched as it is entertaining and accessible, this book is designed to challenge teachers and inform them - as well as encourage them - as they strive to design a twenty-first century learning experience that really does bring the best out of all young people. After all, the future of the world may just depend on it"--Provided by publisher.
Keywords: Teaching; Education -- Aims and objectives; Current events